1979
DOI: 10.1128/jb.140.2.452-458.1979
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide assimilation in cyanobacteria: regulation of ribulose, 1,5-bisphosphate carboxylase

Abstract: Cyanobacteria assimilate carbon dioxide through the Calvin cycle and therefore must regulate the activity of ribulose 1,5-bisophosphate carboxylase. Using an in situ assay, as well as measuring the activity in crude, partially purified, and homogeneous preparations, we can show that a number of phosphorylated intermediates exert a regulatory role. Three diverse organisms, Agmenellum quadruplicatum, Aphanocapsa 6714, and Anabaena sp. CA, were studied, and it was found that the in situ and cell-free carboxylase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 29 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…T h e immediate cessation of cyanobacterial CO, fixation upon transfer from light to dark is accompanied by the appearance of 6PGlu among rapid 14C-and 32P-labelling products ( (Stanier & Cohen-Bazire, 1977). Tabita & Colletti (1979) have found inhibition of activated RuBisCO by exogenous 6PGlu, FBP, fructose 6-phosphate, NADPH and ATP, and activation of inactive RuBisCO by thesecompounds when tested in toluene-permeabilized whole cells of three cyanobacteria. T h e value of using permeabilized whole cells to study RuBisCO regulation in situ has been confirmed with Rhodospirillum rubrum : previous observations in vitro were generally found with the permeabilized cells (Storro & McFadden, 1983).…”
Section: (3) Regulatory Aspectsmentioning
confidence: 93%
See 3 more Smart Citations
“…T h e immediate cessation of cyanobacterial CO, fixation upon transfer from light to dark is accompanied by the appearance of 6PGlu among rapid 14C-and 32P-labelling products ( (Stanier & Cohen-Bazire, 1977). Tabita & Colletti (1979) have found inhibition of activated RuBisCO by exogenous 6PGlu, FBP, fructose 6-phosphate, NADPH and ATP, and activation of inactive RuBisCO by thesecompounds when tested in toluene-permeabilized whole cells of three cyanobacteria. T h e value of using permeabilized whole cells to study RuBisCO regulation in situ has been confirmed with Rhodospirillum rubrum : previous observations in vitro were generally found with the permeabilized cells (Storro & McFadden, 1983).…”
Section: (3) Regulatory Aspectsmentioning
confidence: 93%
“…14C-CABP-labelling of both cytoplasmic and carboxysomal RuBisCO was found after fractionation of the permeabilized cells, indicating that carboxysomal RuBisCO is capable of being activated in situ (Cannon, 1982). T h e action of toluene and chloroform (Tabita, Caruso & Whitman, I 978;Tabita & Colletti, 1979;Cannon, 1982) in rendering cell walls and membranes permeable to RuBP and CABP is evident. However, the effects of these agents on carboxysome membranes, which may lack lipids (Biedermann & Westphal, 1979), is unknown.…”
Section: ( I ) An Active Role In Co Fixation ?mentioning
confidence: 95%
See 2 more Smart Citations
“…This, combined with an unusual asymmetric appearance of the enzyme in the electron microscope, has led to low-molecular-weight estimates of the cyanobacterial enzymes since sedimentation equilibrium analysis of the Synechococcus enzyme yields a molecular weight of 530,000. The enzyme from cyanobacteria contains a typical L8S8 structure (11,65,323,337). However, prior studies had indicated that the Agmenellum and Anabaena enzymes might be composed of only large subunits (L8 structure) (333, 334) and the enzyme from the extreme halophile Aphanothece halophytica was reported to be a tetramer (L4) (60).…”
Section: Structure Of Procaryotic Rubpc/omentioning
confidence: 99%